Bladder Tumor Subtype Commitment Occurs in Carcinoma In Situ Driven by Key Signaling Pathways Including ECM Remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, Johannes; Burger, Maximilian; et al. (Cancer Research, 2021)
Basal and luminal subtypes of invasive bladder tumors have significant prognostic and predictive impacts for patients. However, it remains unclear whether tumor subtype commitment occurs in noninvasive urothelial lesions or in carcinoma in situ (CIS) and which gene pathways are important for bladder tumor progression. To understand the timing of this commitment, we used gene expression and protein analysis to create a global overview of 36 separate tissues excised from a whole bladder encompassing urothelium, noninvasive urothelial lesions, CIS, and invasive carcinomas. Additionally investigated were matched CIS, noninvasive urothelial lesions, and muscle-invasive bladder cancers (MIBC) from 22 patients. The final stage of subtype commitment to either a luminal or basal MIBC occurred at the CIS transition. For all tissues combined, hierarchical clustering of subtype gene expression revealed three subtypes: "luminal," "basal," and a "luminal p53-/extracellular matrix (ECM)-like" phenotype of ECM-related genes enriched in tumor-associated urothelium, noninvasive urothelial lesions, and CIS, but rarely invasive, carcinomas. A separate cohort of normal urothelium from noncancer patients showed significantly lower expression of ECM-related genes compared with tumor-associated urothelium, noninvasive urothelial lesions, and CIS. A PanCancer Progression Panel of 681 genes unveiled pathways specific for the luminal p53-/ECM-like cluster, for example, ECM remodeling, angiogenesis, epithelial-to-mesenchymal transition, cellular discohesion, cell motility involved in tumor progression, and cell proliferation and oncogenic ERBB2/ERBB3 signaling for invasive carcinomas. In conclusion, this study provides insights into bladder cancer subtype commitment and associated signaling pathways, which could help predict therapy response and enhance our understanding of therapy resistance.
CRIS-Team WoS Importer:2021-04-09